ONLINE PROSTITUTION REGISTER ON MICHAT - Catur Priyo Putranto (Faculty of Letters Universitas Balikpapan, 2024)
The birth and development of technology can affect people's behavior. In addition to influencing in a positive direction, the fact is that technology also influences social behavior in a negative direction. One example of negative influence is the rise of online prostitution business practices. Thus, the business practice of prostitution, which is the oldest business practice in the world, can change from traditional to modern. Prostitutes use terms that are only understood by their potential customers. Therefore, the purpose of this study is to find out the form, meaning and function of registers born in the midst of online prostitution business on one of Singapore's dating apps MiChat. The data collection method used is documentation technique. Furthermore, in analyzing the data, classification and interpretation techniques were used, to find out the function of the register I conducted a short conversation on the chat feature. After analyzing the data, this study found forty-eight registers classified into three forms. In addition to the classification into three forms of registers, this study also found several registers that have personal and representational functions.